Design dispersed: forms of migration and flight - Dogramaci, Burcu; Pinther, Kerstin (transcript, 2019)
Design Dispersed pursues the complex and heterogeneous connections between migration and design in the 20th and 21st centuries. The edited volume gathers contributions by international researchers and curators on the question of how design practices and (historical) objects articulate, respond to and critically reflect on migration, flight and displacement: Besides a collage which highlights the aesthetic effects resulting from the networking, overlapping and mixing of forms, another strand of the book looks at the political and social dimensions of design. How are design objects material modes of a critical inquiry on movements of people and things? What role do object trajectories play in the émigré movements of the 1930s and 1940s? Other texts follow the question of how migrants and refugees form their experience and political fight for acceptance into design and architectural productions. A final essay contributes to wordings and projections – what vocabulary do we need in order to adequately think and write about a design dispersed? [Verlagshomepage]
Literaturangaben
Impressum: "Extended publication on the conference 'Design Dispersed. Forms of Flight and Migration' ... at the Institute for Art History, Ludwig Maximilian University of Munich and at the Zentralinstitut für Kunstgeschichte, Munich, 9-11 February 2017"
Keywords: Konferenzschrift -- 2017 -- München; Geschichte 1900-2019; Interkulturalität; Architektur; Design; Flucht; Exil; Migration; Geschichte 1933-2019